(untitled) (Journal of Pharmaceutical Negative Results, 2022)
BACKGROUND: Self medication is the use of drugs to treat self diagnosed disorders or symptoms or continued use of a prescribed drug for chronic or recurrent diseases or symptoms. OBJECTIVES: To assess the prevalence of self medication among the adult population of urban Chennai and to measure the association between socio demographic factors and self medication among urban adult population. MATERIALS AND METHODS: A community based cross sectional study was conducted in the urban field practice area of ACS Medical College (Nerkundram) in Chennai, India during the month of June 2022 using a structured questionnaire among adult population. The study population included 290 people aged 18 years and above. Data was collected by house to house survey using a pre designed questionnaire and analysed using SPSS 25 version. Simple proportions were calculated and chi-square test was applied for statistical significance, p value less than 0.05 was considered as statistically significant. RESULTS: The prevalence of self medication was found to be 52.8% out of which 59.6% were males. Anti-pyretics (73.9%) and antibiotics (48.4%) were the most commonly used by the participants. Fever was the most common morbidity (34.4%), followed by common cold (24.8%) for which the study participants self‑medicated. Gender, occupation and educational status are associated with self medication and were statistically significant. CONCLUSION:. Self‑medication is an important public health problem in this study area. Regulation of pharmacies and health education of the public may help in limiting the self‑medication practices.